Computer-aided process engineering (CAPE): education and practice - Mohd Yusof, Khairiyah; Kamsah, Mohd Zaki; Abdul Aziz, Badhrulhisham (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1994)

(untitled)
In this paper, the important roles of computer-aided tools in solving problems in process engineering are highlighted. Few research which have been done in the area of CAPE are focused on and results from these research is reported. The future direction of CAPE is also presented.